2012
DOI: 10.5430/jst.v2n4p38
|View full text |Cite
|
Sign up to set email alerts
|

Double reading for gross tumor volume assessment in radiotherapy planning

Abstract: Background/Objective: The precise definition of the gross tumor volume (GTV) that takes into account intra-and interobserver variability is necessary for high-precision radiotherapy (RT) techniques. The purpose of this study was to demonstrate the practical GTV assessment by a "double reading" approach.Methods: Pretreatment magnetic resonance (MR) imaging, including the post-contrast 3D magnetization-prepared rapid-gradient echo (MP-RAGE) sequence (section thickness 1.0 mm) was performed on a 3T superconductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Where studies have looked at the similarities or agreement in observers, they have tended to use brain tumour delineation tasks. Low inter- and intra-observer variability is well documented in clinicians delineating brain tumours (Crowe, Alderson, Rossiter, & Kent, 2017 ; Mazzara, Velthuizen, Pearlman, Greenberg, & Wagner, 2004 ; Murakami, Hirai, Toya, Nakamura, & Yamashita, 2012 ; Weltens et al, 2001 ). This line of research highlights the need to obtain high agreement in tasks relevant to medical image perception to assure consistency both within and between clinicians responsible for making diagnostic decisions.…”
Section: Experiments 1b: Independent-slicesmentioning
confidence: 99%
“…Where studies have looked at the similarities or agreement in observers, they have tended to use brain tumour delineation tasks. Low inter- and intra-observer variability is well documented in clinicians delineating brain tumours (Crowe, Alderson, Rossiter, & Kent, 2017 ; Mazzara, Velthuizen, Pearlman, Greenberg, & Wagner, 2004 ; Murakami, Hirai, Toya, Nakamura, & Yamashita, 2012 ; Weltens et al, 2001 ). This line of research highlights the need to obtain high agreement in tasks relevant to medical image perception to assure consistency both within and between clinicians responsible for making diagnostic decisions.…”
Section: Experiments 1b: Independent-slicesmentioning
confidence: 99%
“…Low inter-observer agreement was also observed amongst nine physicians delineating five patients’ supratentorial inoperable brain tumors on CT scans (range 38–59%) and on CT combined with MRI scans (range 38–71%; Weltens et al, 2001 ). Murakami et al (2012) revealed an average concordance rate of 82% for one radiation oncologist and one neuroradiologist delineating glioblastomas using diagnostic MR images whilst Mazzara et al (2004) reported an average concordance rate of 28% for three radiation oncologists outlining gliomas on MR images. Researchers have also revealed high intra-observer variability with Mazzara et al (2004) reporting only a 20% concordance rate for three radiation oncologists delineating tumors at three 1-month intervals.…”
Section: Introductionmentioning
confidence: 99%
“…The area on which two clinicians agree (i.e., they draw around the same tissue) is commonly referred to as the intersection area. A concordance rate (note: researchers refer to this value differently but it reflects the same calculation) ranging from 0% (complete disagreement) to 100% (complete agreement) can be calculated by dividing the intersection area by the sum of the area contoured by both clinicians ( Murakami et al, 2012 ) to index inter-observer agreement. Leunens et al (1993) reported that the concordance rate of 12 radiation oncologists delineating 5 patients’ brain tumors on lateral orthogonal radiographs ranged from 25 to 73%.…”
Section: Introductionmentioning
confidence: 99%